Blood Redox Status in Men and Women at Rest - Oikonomou Δημήτριος; Misailidi Μαρία; Theodorou Αναστάσιος; Sakellariou Γιώργος; Paschalis Βασίλης; Nikolaidis Μιχάλης; Alexiou Βασίλης; Jamurtas Αθανάσιος (Inquiries in Physical Education and Sport, 2009)
The aim of the present study was to examine selected blood redox status indices in young women and men at rest. Forty four healthy untrained men and women were equally divided into two groups by sex. Blood samples were obtained and analyzed for reduced glutathione (GSH), oxidized glutathione (GSSG), GSH/GSSG ratio, protein carbonyls, thiobarbituric acid reactive substances (TBARS), catalase and total antioxidant capacity (TAC). Blood was collected from women while they were in luteal phase at their menstrual cycle. Statistical analysis did not demonstrate any significant differences in the selected blood redox status indices (p>.05) between men and women. In conclusion, this study did not reveal differences in blood redox status between men and women suggesting that gender does not affect blood redox status.